SPEECH FUNCTIONS USED IN CLASSROOM INTERACTION OF THE ELEVENTH GRADE STUDENTS AT MA NURUL IKHWAN KONSESI - Tri Ardiansyah; Meisuri Meisuri (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This study aimed at describing the use of speech functions and investigating the reasons of using the most dominant speech functions in classroom interaction at MA Nurul Ikhwan Konsesi. The objectives of this study were to indicate the types of speech function in the teacher-student classroom interaction and to describe the pattern of speech function realized in the teacher-student classroom interaction. The method used in this research was descriptive qualitative research. The data were collected by observing, recording the utterances of teacher and eleventh-grade students at MA Nurul Ikhwan Konsesi. The data were analyzed based on Systemic Functional Linguistics theory. There were 198 utterances produced as the total number consisting of 55 (28.80%) statement, 80 (42.39%) questions, 10 (5.44%) commands, 3 (0.54%) offer, 37 (19.02%) answers, 8 (3,27) disclaimers, and 3 (0.54%) acknowledgement. The teacher produced 150 (77.17%) utterances and students produced 48 (22.83%) utterances. The result showed that the question was the dominant type of speech functions used by the teacher, and the answer was the dominant type of speech function responses used by the students.Keywords: Speech Functions, Classroom Interaction, Mood System.